Note de recherche: "Phu-ying-kham-phet vs. kathoey" : l'évolution du (trans)genre et l'émergence de l'identité de transfemale en Thaïande contemporaine - Thongkrajai, Cheera (Anthropologica, 2014)
In 2010, Thai people discovered the term phu-ying kham-phet, translated from transfemale or transsexual female in English, on a TV show. This has generated public debates and controversies in the social media and within Thai lesbian, gay, bisexual and transgender (LGBT) communities. This article, based on facts and data from the internet, social media, TV shows, discusses the emergence of the phu-ying-kham-phet category and different positions of LGBT agencies. The article tries to understand the conception of phet (sex/gender), and to show distinction and diversity of transgender identities, social and political positions and stakes in the (trans)gender evolution in contemporary Thailand.